Empowering local communities through collective grassroots actions: The case of "No Al Progetto Eleonora" in the Arborea District (OR, Sardinia). Issue 1 (2nd January 2017) - Ruiu, Maria Laura; Ragnedda, Massimo
ABSTRACT: This article explores both how local social committees may contribute toward generating collective actions, leading local communities to empower their environment, and how new information communication technologies (ICTs) may alter the collective action. It focuses on a case study, represented by the "No al Progetto Eleonora" local committee that operates in the Arborea district of Oristano, in Sardinia, Italy. Here, the community has become progressively cohesive in the face of an external environmental threat represented by the proposal for a drilling project. In this context, the role played by the Internet has been marginal in promoting community cohesion, even if it has indirectly enhanced it. In other words, the Internet played a marginal role in promoting the protest and reinforcing community cohesion, but it played a primary role in attracting external solidarity and support, thus indirectly reinforcing the sense of community against an external threat.